1984
DOI: 10.1111/j.1600-0722.1984.tb00909.x
|View full text |Cite
|
Sign up to set email alerts
|

Short term fasting and lactovegetarian diet does not affect human saliva

Abstract: – Forty‐two adults, visiting a Swedish health home, participated in the investigation, which included a 6‐day period of fasting, followed by a 6‐day period with a lactovegetarian diet. The results obtained indicated only a minor and mostly not significant influence on secretion rate, buffer effect, concentration of various electrolytes, and number of lactobacilli and S. mutans of whole saliva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
2
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…Even in persons who consumed exclusively sweet beverages, no associations was found. That is in accordance with previous reports (8)(9)(10).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Even in persons who consumed exclusively sweet beverages, no associations was found. That is in accordance with previous reports (8)(9)(10).…”
Section: Discussionsupporting
confidence: 94%
“…However, according to Table 5, demonstrating the results of stepwise analysis of regression, the protein variable did not fit into the model explaining most of the buffer variation. The result is in accordance with previous experimental studies (8)(9)(10), but at variance with others (6, 7).…”
Section: Discussionsupporting
confidence: 93%
“…Within 7 wk after the start of the counselling, however, 79% of the experimental group reduced their numbers of lactobacilii to the same level as control group B had at the start. According to previous studies, the oral concentration of lactobacilii drops after consumption of carbohydrates is reduced I (9)(10)(11)(12)(13)(14). The results suggest that the counselling tnethod applied in the present study motivated the participants to reduce sugar consumption to an extent that could be verified by a reduced lactobacillus count in saliva and eventually by a reduced caries activity.…”
Section: Discussionsupporting
confidence: 68%
“…This study showed that there was a shghtly higher buffer capacity and pH for the vegetarian group, without reaching statistical significance. Previous studies on diet and buffer capacity have produced conflicting results (7,8,(18)(19)(20)(21)(22)(23). However, the most consistent finding is that vegetables and fruits yield an increase in buffer capacity (7,18,19,21).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the secretion rate as well as the buffer capacity in whole saliva was increased when 20 omnivores changed to a lacto-vegetarian diet (7). There are also studies that have shown no relationship to different diets (5,8,22,23). However, many studies indicate that an increased intake of vegetables and fruits is positively related to a higher buffer capacity (7,18,19,21).…”
mentioning
confidence: 99%